Literary Significance of Number Archetypes - o‘g‘li, Umarov Umidjon Akram (Indonesian Journal Publisher, 2024)
This article explains the importance of number archetypes, putting emphasize on their roles as symbols that transcend simple numerical value to show deeper meanings and functions across various cultures and their literature. In this work, main number archetypes are also highlighted. For instance, three embodies unity in diversity, seven symbolizes spirituality and perfection, and twelve represents wholeness and order. These symbol archetypes not only contribute layers of meaning to literary works but also facilitate the expression of complex themes and universal truths. By connecting these archetypes to religious texts, myths, and cultural traditions, this article explores that numbers can enrich narratives and provide insight into human experiences. Finally, the discussion presents the examination of number archetypes in literature as a creative pathway to improve our understanding of reality and cultural way of storytelling.